Lucha of the forgotten spring - Mejia, Tehlor Kay (New York : Make Me A World, 2025)
Lucha Moya is back in Robado to settle unfinished business and eradicate olvida, the forgetting drug, but Lucha must face long-avoided fears to save the people she cares for, in the second book of a Latine folklore-inspired duology.
Keywords: Sisters -- Juvenile fiction; Magic -- Juvenile fiction; Forests and forestry -- Juvenile fiction; Drugs -- Juvenile fiction; Self-realization -- Juvenile fiction; Young adult fiction; Fantasy fiction